Geguritan Majalah Panjebar Semangat: Materi Ajar Apresiasi Sastra Berbasis Pendidikan Budi Pekerti (DIWANGKARA: Jurnal Pendidikan Bahasa, Sastra dan Budaya Jawa, 2021)
This research is a qualitative descriptive research under the background of the importance of inculcating the value of character education to high school students through learning of Javanese literature appreciation, especially geguritan. The purpose of this study is to describe and interpret the value of character education in the geguritan of Panjebar Semangat magazines. The method used is a documentation study. The data were collected by carefully reviewing and transcribing the meaning of each geguritan and taking notes. The data analysis was carried out using a qualitative descriptive technique using the Miles and Huberman model, namely the steps of identifying the research focus, reducing data, analyzing and presenting data, and making inferences. The results of this study indicate that the geguritan in the Panjebar Semangat magazines contain the values of character education which include: religiosity, sociality, fairness, honesty, responsibility, independence, awareness toward environment. Through geguritan in the Panjebar Semangat magazines, the authors would like to convey messages to the readers to become human beings with strong characters.
Keywords: Appreciation of Javanese Literature; Character; Geguritan